2022
DOI: 10.1186/s41232-021-00186-3
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of inflammation-mediated endothelial–mesenchymal transition in health and disease

Abstract: Endothelial–mesenchymal transition (EndoMT), a cellular differentiation process in which endothelial cells (ECs) lose their properties and differentiate into mesenchymal cells, has been observed not only during development but also in various pathological states in adults, including cancer progression and organ/tissue fibrosis. Transforming growth factor-β (TGF-β), an inflammation-related cytokine, has been shown to play central roles in the induction of EndoMT. TGF-β induces EndoMT by regulating the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 93 publications
(175 reference statements)
4
43
0
Order By: Relevance
“…Our study also found that the expressions of TNF-α, IL-6, IL-1β and MPO level were increased in BLM-treated rats, in accordance with other studies using the same animal model [34]. It is widely accepted that in ammation response contributes to the development of EMT, which plays a crucial role in driving the PF development [51,52]. It has been reported that TNF-α induced EMT was through activation of Akt/NF-κB (nuclear factor kappa B) pathway in a renal allograft interstitial brosis [53].…”
Section: Discussionsupporting
confidence: 91%
“…Our study also found that the expressions of TNF-α, IL-6, IL-1β and MPO level were increased in BLM-treated rats, in accordance with other studies using the same animal model [34]. It is widely accepted that in ammation response contributes to the development of EMT, which plays a crucial role in driving the PF development [51,52]. It has been reported that TNF-α induced EMT was through activation of Akt/NF-κB (nuclear factor kappa B) pathway in a renal allograft interstitial brosis [53].…”
Section: Discussionsupporting
confidence: 91%
“…Wang et al 2019). Finally, TGFβ signaling is linked to the response of endothelial cells to inflammation in COVID-19 (Yoshimatsu and Watabe 2022). Together, these results build on previously reported evidence to show that multiple signaling pathways in the heart undergo both cell type-specific and systemic changes in response to COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that activated FGFR1 recruits FRS2α, which induces let-7 microRNA expression and suppresses the expression of TGFβRI [ 89 , 90 ]. However, inflammatory cytokines, including TNF-α, IFN, and IL-1β, inhibit FGFR1 signaling and enhance EndoMT in some cultured endothelial cells [ 91 ].…”
Section: Signaling Pathways Involved In the Regulation Of Endomtmentioning
confidence: 99%
“…Extensive research has been conducted to elucidate the occurrence of EndoMT in in vitro studies. EndoMT is defined in these studies as cells that exhibit the following characteristics: (1) loss of endothelial properties, (2) coexpression of endothelial and mesenchymal markers, (3) increased migration, and (4) increased mesenchymal and myofibroblastic cells [ 23 , 91 ]. For example, Krenning et al demonstrated that when human umbilical cord endothelial cells (HUVECs) were passaged and cultured with TGF-β1 and PDGF-BB, these cells lost their endothelial markers and developed spindly shapes while gaining the capacity to produce a variety of fibroblast-specific molecules.…”
Section: Endomt In In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation